Investigation of steatosis profiles induced by pesticides using liver organ-on-chip model and omics analysis. (June 2021) - Jellali, Rachid; Jacques, Sebastien; Essaouiba, Amal; Gilard, Françoise; Letourneur, Franck; Gakière, Bertrand; Legallais, Cécile; Leclerc, Eric
Abstract: Several studies have reported a correlation between pesticides exposure and metabolic disorders. Dichlorodiphenyltrichloroethane (DDT) and permethrin (PMT), two pesticides highly prevalent in the environment, have been associated to dysregulation of liver lipids and glucose metabolisms and non-alcoholic fatty liver disease (NAFLD). However, the effects of DDT/PMT mixtures and mechanisms mediating their action remain unclear. Here, we used multi-omic to investigate the liver damage induced by DDT, PMT and their mixture in rat liver organ-on-chip. Organ-on-chip allow the reproduction of in vivo -like micro-environment. Two concentrations, 15 and 150 μM, were used to expose the hepatocytes for 24 h under perfusion. The transcriptome and metabolome analysis suggested a dose-dependent effect for all conditions, with a profile close to control for pesticides low-doses. The comparison between control and high-doses detected 266/24, 256/24 and 1349/30 genes/metabolites differentially expressed for DDT150, PMT150 and Mix150 (DDT150/PMT150). Transcriptome modulation reflected liver inflammation, steatosis, necrosis, PPAR signaling and fatty acid metabolism. The metabolome analysis highlighted common signature of three treatments including lipid and carbohydrates production, and a decrease in amino acids and krebs cycle intermediates. Our study illustrates the potential of organ-on-chip coupled to multi-omics for toxicological studies and provides new tools for chemical risk assessment. Highlights: Rat liver organ-on-chip model was used to study pesticides toxicity. The model was exposed to DDT, permethrin and their mixtures at 15 and 150 μM. Transcriptome and metabolome profile showed a dose-dependent effect. Liver steatosis, inflammation and cell death were common signature for high-doses. Mixture of DDT and PMT led to additive and increased effects.